Olfactory receptor OR51B5 suppressed esophageal cancer progression through activates Calcium / N-Ras signaling - Fan Yang; Jiaqi Yang; Chengbo Zhu; Tianyi Ding; Xiaoyu Zhang; He Zhang (Cell Death and Disease)
Abstract The transcriptional regulation of olfactory receptors (ORs) plays a critical role in various biological processes, and has recently been considered a potential therapeutic target for cancer treatment. Esophageal cancer (EC) is a highly invasive neoplasm with dismal prognosis, but the specific roles of ORs in EC remain largely unexplored. Here, we developed a comprehensive workflow to identify potential functional olfactory receptor family 51 subfamily B member 5 (OR51B5) and demonstrated that OR51B5 locus acted as a key spatial element contributing to the progression of esophageal cancer. Moreover, we showed that the CTCF-EZH2 enhanced the trimethylation of lysine 27 of histone H3 (H3K27me3) and increased repressive and closed chromatin state at the OR51B5 promoter region. Subsequently we demonstrated that closed chromatin impaired the entry of RNA polymerase II and inhibited the transcription of OR51B5, thereby causing N-Ras activation and promoting tumor cell proliferation and metastasis. Our study provides an alternative workflow for discovering critical regulatory sites for control tumorigenesis, and reveals a novel OR51B5 triggering mechanism underlying esophageal cancer progression.